Oxidation-responsive micelles by a one-pot polymerization-induced self-assembly approach. Issue 13 (11th January 2018) - Sobotta, Fabian H.; Hausig, Franziska; Harz, Dominic O.; Hoeppener, Stephanie; Schubert, Ulrich S.; Brendel, Johannes C.
Abstract : Combining a sequential, one-pot RAFT polymerization with the polymerization-induced self-assembly process results in a versatile oxidation-responsive carrier system. Abstract : The increased levels of reactive oxygen species (ROS) such as hydrogen peroxide in inflamed or cancerous tissue represent a promising trigger for the local and selective release of drugs at the affected areas. Despite new developments in the field of oxidation-responsive drug carrier systems, the preparation of the required materials remains in most cases tedious. Here, we present a novel system, which combines the advantages of a one-pot sequential controlled radical polymerization with the direct polymerization-induced self-assembly (PISA) process. By utilizing highly reactive acrylamide monomers, full conversion can be reached while maintaining a high chain end fidelity in RAFT polymerization, which enables the precise preparation of block copolymers or micelles, respectively, without intermediate purification steps. We demonstrate that the cyclic thioether N -acryloyl thiomorpholine is a versatile monomer for PISA resulting in a hydrophobic block, which upon oxidation can be transformed into a highly water-soluble sulfoxide. The micellar structures are tunable in size by the variation of the block length and feature a good sensitivity towards hydrogen peroxide even at low concentrations of 10 mM resulting in their disintegration. In vitro studies prove the uptake of these micelles into cells without signs of toxicity up to 500 μg mL −1 . The straightforward preparation, the excellent biocompatibility and the selective disintegration in the presence of biologically relevant levels of hydrogen peroxide are features that certainly make the presented system an attractive new material for oxidation-responsive drug carriers.